Environmental radioactivity at the Peruvian Scientific Station "Machu Picchu": Cs-137, Ra-226, Be-7 and K-40 concentrations in Antarctic samples by gamma spectrometry - Gonzáles, Susana (2002)
In order to continue with the Research Program in Environmental Radioactivity in the Antarctic Region initiated in 1996, the Peruvian Institute of Nuclear Energy (IPEN) participated in the 11th Scientific Expedition to Antarctica (ANTAR XI) on 2000. The main objective of this study is to evaluate environmental components for achieving a baseline study related to artificial and natural radioactivity level. For this purpose, samples of brown macro-algae (Phaeophyta), lichen, moss, gramineous, soil, marine sediment, sea water and air were collected in the surrounding area of the Machu Picchu Scientific Station. The physical, radiochemical treatment and radiometric assays of the samples were done in the Environmental Control Department of the "RACSO" Nuclear Center. The presence of anthropogenic radionuclide Cs-137, in some antarctic environmental components, confirms that this element was dispersed globally after the nuclear testing carried out in other latitudes. The environmental radiological impact in the antarctic ecosystem has been minimum due to the low levels of found radioactivity. In general, lichens seem to accumulate more Cs-137 than other biological components.